Bookpanda and GrabBook Management System - Zainudin, Nur Aina Syazwina; Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2024)
The BookPanda and GrabBook Management System is a web-based platform designed to address school library management challenges. It resolves issues such as borrowing management, data mismanagement, and duplication, boosting administrative productivity. The system eases the administrator's burden with library prefects assisting in borrowing operations, while students can review fines and borrowing records. The technology combines AI, NLP, and machine learning to develop an intelligent chatbot for enhanced user engagement. A recommendation system utilizing the Cosine Similarity algorithm is integrated via Flask, offering customized book suggestions. The prototyping methodology ensured a user-centric design, resulting in a practical and high-quality web-based system developed using Visual Studio Code and a MySQL database. Accessible from library helpdesk computers, it significantly benefits administrators, the library, and students, particularly during peak hours, enhancing the user experience. This system aims to automate tasks, save time, and improve library management efficiency, focusing on scalability and enhanced user services.